2020
DOI: 10.7150/thno.38483
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric regulation of protein 14-3-3ζ scaffold by small-molecule editing modulates histone H3 post-translational modifications

Abstract: Background: Histone post-translational modifications (PTMs) are involved in various biological processes such as transcriptional activation, chromosome packaging, and DNA repair. Previous studies mainly focused on PTMs by directly targeting histone-modifying enzymes such as HDACs and HATs.Methods and Results: In this study, we discovered a previously unexplored regulation mechanism for histone PTMs by targeting transcription regulation factor 14-3-3ζ. Mechanistic studies revealed 14-3-3ζ dimerization as a key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The posttranslational modification of proteins refers to the chemical modification of proteins after translation; these modifications can regulate the activity, localization and folding of proteins and their interactions with other biological macromolecules [ 1 ]. An increasing number of studies have shown that posttranslational modifications (PTMs) are major determinants of the structure of chromatin and play key roles in the regulation of functional gene expression profiles to enhance the diversity of protein species and functions of organisms [ 2 , 3 ]. Lysine is one of the amino acids in proteins that is the most frequent site of posttranslational modifications [ 4 ], such as acetylation [ 5 ], ubiquitination [ 6 ], butyrylation [ 7 ], malonylation [ 8 ] and succinylation.…”
Section: Introductionmentioning
confidence: 99%
“…The posttranslational modification of proteins refers to the chemical modification of proteins after translation; these modifications can regulate the activity, localization and folding of proteins and their interactions with other biological macromolecules [ 1 ]. An increasing number of studies have shown that posttranslational modifications (PTMs) are major determinants of the structure of chromatin and play key roles in the regulation of functional gene expression profiles to enhance the diversity of protein species and functions of organisms [ 2 , 3 ]. Lysine is one of the amino acids in proteins that is the most frequent site of posttranslational modifications [ 4 ], such as acetylation [ 5 ], ubiquitination [ 6 ], butyrylation [ 7 ], malonylation [ 8 ] and succinylation.…”
Section: Introductionmentioning
confidence: 99%
“…The cell lysates were obtained by five repeated freeze-thaw cycles in liquid nitrogen. The soluble lysates were centrifuged, and supernatants were detected by a western blot (Wan et al, 2020).…”
Section: Cetsamentioning
confidence: 99%
“…PTA was detected in brain tissue after 0.5 h, suggesting that PTA has the potential to cross the blood-brain barrier. In addition, previous results also showed that PTA decreased the cerebral infarction area against MCAO insult, indicating that PTA treatment had a protective effect on cerebral ischemia . However, there are limited reports on the clinical application of PTA.…”
Section: Introductionmentioning
confidence: 95%
“…Caesalpinia sappan L., as a member of the leguminous plant family, exhibits therapeutic potential for burning sensations, leprosy, skin diseases, dysentery, and diabetic complications in China and other Asian countries . Protosappanin A (PTA) is a dibenzoxocin derivative from the medicinal plant Caesalpinia sappan L. PTA mediates a variety of signaling proteins such as NF-κB, histone H3, and AKT-mTOR, which has been found to exert multiple bioactive effects including anti-inflammatory, antibacterial, and antioxidative stress activities. Furthermore, previous reports have suggested that PTA has an immunosuppressive activity which promotes cardiac allograft survival, diminishes inflammatory cell infiltration, and inhibits interferon γ-induced protein 10 . Moreover, PTA has been reported to inhibit CD 4+ /CD 8+ ratios of peripheral T cells and the resultant neuroinflammatory response through the down-regulating JAK2/STAT3-dependent inflammation pathway. , Notably, previous studies have shown that PTA and oleanolic acid (OA) can inhibit apoptosis in injured podocytes, accompanied by increased protein levels of nephrin, podocin, CD2AP, and Bcl-2 and decreased levels of desmin and Bax, indicating that PTA may be a versatile neuroprotective agent …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation